PREVALENCE OF BUXTONELLA SULCATA IN NEONATAL ANDYOUNG CALVES IN AL-NASIR STATION AND SOME REGIONS INBAGHDAD (AL-SHUALA SND GAZALIYA) - Al-Zubaidi, Mohammad; Al-Mayah, Kasim (Iraqi Journal of Science, 2024)
Neonatal diarrhea of calves is a major cause of economic loss in rearing youngcalves. Buxtonella sulcata may be a potential cause of diarrhea in these animals.This study aimed to investigate the prevalence of B. sulcata infection and its role indiarrhea in neonatal and young calves. A total of 250 fecal samples were collectedfrom calves (110 male and 140 female, ages ranged 1-30 day, among which 98 haddiarrhea). Two laboratory tests were used to detect B. sulcata cysts and trophozoitesin fecal samples which are direct wet film method and ether-formalin sedimentationmethod. The overall rate of infection was 43.2%. There is a significant difference inthe rate and intensity of infection between calves with and without diarrhea. Calvesover 10 days old had higher rate of infection than calves under 10 day old withsignificant difference. B. sulcata may be a potential cause of diarrhea in neonataland young calves when there is suitable conditions in the intestinal lumen thatpromote the parasite multiplication.